Interaksi Genotipe x Lingkungan dan Stabilitas Hasil Biji Kedelai Toleran Naungan - Sundari, Titik; Nugrahaeni, Novita; Susanto, dan Gatut Wahyu Anggoro (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2016)
ABSTRACTTwelve soybean shade tolerant promising lines and two check varieties, Pangrango and Argomulyo, were evaluated in eight locations covered varying degree of shades. The objective of this study was to assess the effect of genotype x environment interaction on seed yield and yield components, as well as on adaptation and yield stability of the lines  under those environments. The trial, in each location, was arranged in randomized block design repeated four times. The traits evaluated were days of flowering, maturity days, plant height, pod number, 100 seed weight, and seed yield. Light intensity was measured during generative phase, started at plants’ 30 days old,  two week interval. The results showed that genotype x environment interaction significantly affected those evaluated traits. Stability analysis revealed that four lines, i.e., IBK5-173-5-372, IBM22-861-2-22, IBM22-862-4-1, and IBM22-867-4-7 poorly adapted to the environments as indicated by coefficient regressions approximating 1.0 and low yield average. Eight lines, i.e., IBK5-143-3-7, IBK5-147-2-11, IBK5-172-4-36, IBK5-173-5-371, IIj9-299-1-4, IBM22-873-1-13, IBIj11-431-2-20, and AI26-1114-8-28, and the two check varieties, Pangrango and Argomulyo, were unstable. Of the 13 unstable genotypes, two lines, AI26-1114-8-28  and IBM22-873-1-13, gave higher average yield under shade condition (35%-70% shading level), 1.68 t/ha and 1.36 ton ha-1, respectively, than the two check varieties.Keywords: adaptation, Glycine max